Traces of Jan Kochanowski in Eighteenth-Century Literary Theory and Epigrammatic Poetry - Vaškelienė, Asta (Senoji Lietuvos literatūra, 2024)
The article addresses the relevance of Jan Kochanowski, a Polish-Lithuanian Renaissance poet, in the discourse of literary theory and in practical creative work in the eighteenth century. The first part of the article examines the manner and the extent that Kochanowski is mentioned in the most important printed poetic and rhetorical works of the period under scrutiny. The second part discusses some examples of eighteenth-century epigrammatic works written in Lithuania, looking for their points of contact with Jan Kochanowski’s literary tradition.The study reveals that Jan Kochanowski figures in the discourse of eighteenth-century literary theory as a writer of threni, satires, and dramas, but his example is not used to explain the theory of the genre of the epigram. Only Franciszek Dmochowski, the only one of the authors of poetics, mentions Kochanowski as a poet of witty epigrams (fraszki). Kochanowski’s epigrammatic tradition did not find any followers in eighteenth-century Latin epigrammatic poetry in the Grand Duchy of Lithuania, but the short jokes (żarty) may indicate its reception in the poetry in Polish of the second half of the eighteenth century.
Keywords: Jan Kochanowski; epigram; occasional poetry; poetics; rhetoric; genre